Initiation of hydrogen induced cracks at secondary phase particles (Fracture and Structural Integrity, 2020)
The goal of this work is to propose a general mechanism for hydrogen induced crack initiation in steels based on a microstructural study of multiple steel grades. Four types of steels with strongly varying microstructures are studied for this purpose, i.e. ultra low carbon (ULC) steel, TRIP (transformation induced plasticity) steel, Fe-C-Ti generic alloy, and pressure vessel steel. A strong dependency of the initiation of hydrogen induced cracks on the microstructural features in the materials is observed. By use of SEM-EBSD characterization, initiation is found to always occur at the hard secondary phase particles in the materials.
Keywords: Blisters; hydrogen induced cracking; particles; secondary phase; scanning electron microscopy